Kearifan Lokal Komunitas Kampung Tambak Anyar dalam Menghadapi Baah dan Baah Labung, 1980-2000 - Sayyidati, Rabini (Mahesa Research Center (PT. Mahesa Global Publishing), 2022)
The problem of this research is the phenomenon of floods and flash floods (baah dan baah labung in Banjarese term) that often hit the Batang Banyu Riverbank community, Tambak Anyar Martapura, Banjar Regency, especially in 1980-2000. The arrival of baah and baah labung every year, apparently does not cause the Batang Banyu Tambak Anyar riverbank community to move to a higher place, but they are actually very strong in surviving in the village, even the settlements are increasing year by year. This research method uses the historical method. Sources of data in this study are through written sources which are the archives of the Head of Padang Tambak Anyar, village monographs from 1980-2000, archives from ANRI (National Archives of the Republic of Indonesia), relevant books. Oral sources based on the results of interviews with informants who know about the events of 1980-2000 and understand the strategies for dealing with baah and baah labung. While the source of objects, is a source that is in accordance with the context of the location of events and objects that are directly related to the events. The results showed that the Batang Banyu Tambak Anyar Martapura community, Banjar Regency, 1980-2000, for 20 years had their own strategy derived from local genius to deal with baah and baah labung so that they are always ready to face this annual natural disaster.